2015
DOI: 10.1186/s12966-015-0268-3
|View full text |Cite
|
Sign up to set email alerts
|

Parenting around child snacking: development of a theoretically-guided, empirically informed conceptual model

Abstract: BackgroundSnacking contributes to excessive energy intakes in children. Yet factors shaping child snacking are virtually unstudied. This study examines food parenting practices specific to child snacking among low-income caregivers.MethodsSemi-structured interviews were conducted in English or Spanish with 60 low-income caregivers of preschool-aged children (18 non-Hispanic white, 22 African American/Black, 20 Hispanic; 92 % mothers). A structured interview guide was used to solicit caregivers’ definitions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 37 publications
(36 reference statements)
4
46
0
Order By: Relevance
“…Indeed, review of the audio tapes indicated that most families were engaging in food or mealtime preparation activities during this time. This is also a time of day when children are most likely to snack (Wang et al, 2016), and the need to examine “food parenting” around snacking has recently been highlighted (Davison et al., 2015). Some parents view snacks as a quick way to “tide a child over” until mealtime (Younginer et al., 2016), for example, whereas others offer children food on a fixed schedule but do not consider this snacking (Jacquier, Gatrell, & Bingley, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, review of the audio tapes indicated that most families were engaging in food or mealtime preparation activities during this time. This is also a time of day when children are most likely to snack (Wang et al, 2016), and the need to examine “food parenting” around snacking has recently been highlighted (Davison et al., 2015). Some parents view snacks as a quick way to “tide a child over” until mealtime (Younginer et al., 2016), for example, whereas others offer children food on a fixed schedule but do not consider this snacking (Jacquier, Gatrell, & Bingley, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some parents view snacks as a quick way to “tide a child over” until mealtime (Younginer et al., 2016), for example, whereas others offer children food on a fixed schedule but do not consider this snacking (Jacquier, Gatrell, & Bingley, 2017). Parents seem to use a range of strategies to manage child snack intake (Boots et al., 2016) but in general food parenting outside of mealtimes, particularly as it occurs in naturalistic settings, is not yet fully understood (Davison et al, 2015; Jacquier et al, 2017). Prior work also suggests that family stress arises around managing child needs, specifically hunger, while attempting meal preparation (Norman et al, 2015), and maternal stress due to limited time for meal preparation has frequently been reported (Beshara, Hutchinson, & Wilson, 2010; Devine, Connors, Sobal, & Bisogni, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As reviewed by Davison et al (2015), child snacking (including soda consumption) is on the rise in the US, contributing a significant proportion of children's daily caloric intake and constituting a key source of 'empty' calories. Concern over these dietary behaviours is reinforced by the findings of longitudinal research that suggests that unhealthy snacking behaviours and soda intake are associated with increases in child adiposity (Shroff et al, 2014).…”
mentioning
confidence: 99%